Dominasi Atas Perempuan-Alam dalam Cerpen Sumur Karya Muna Masyari (Kajian Ekofeminisme) - Imawati, Endah; Retnosari, Putri (Jurnal Pena Indonesia, 2025)
This study aims to describe the deconstruction of excessive use of nature and the environment and ignoring the values ​​of local wisdom. This qualitative study uses ecofeminist thinking with the data source of the short story "Sumur" by Muna Masyari. The results of this study show the struggle of women to maintain nature and the environment that has provided local wisdom when a long drought hits. Women’s struggle is in line with ecofeminist thinking while rejecting the use of nature and the environment that is not in accordance with local wisdom.